Kajian Teologis Tentang Moderasi Beragama dalam Pandangan Paulus - Adheline Novita Swandini (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This article examines the Apostle Paul's views on religious moderation, revealed through an analysis of his letters in the New Testament. Paul had main goals, including building unity in diversity, teaching attitudes of love and forgiveness, advancing the principles of faith as a connector, encouraging attitudes of tolerance, and spreading the teachings of Christ inclusively. This article explains how Paul guides the Christian community to live in harmony, respect, and embrace diversity in the Christian faith.